DEVELOPMENT OF ENTERPRISES BASED ON FINANCIAL INSTRUMENTS (World Economics and Finance Bulletin, 2024)
This paper employs generalized methods of moment (GMM) to analyze the enterprise data set collected from the General Statistics Office in the period 2015–2022 to provide insight on the influence of financial development on business growth: the case of the Southern Key Economic Zone (SKEZ). The empirical results indicate that financial development plays an important role in business growth. However, providing financing to offset scale has the potential to increase sales but reduce business growth.
Keywords: Bank profitability; accounting indicators of profits; future profit forecasts